FILM “TANDA TANYA” SEBAGAI PRODUK BUDAYA POPULER DAN PERANNYA DALAM KONTEKS PLURALISME AGAMA DI INDONESIA - Nelson Semol Kalay (Institut Agama Kristen Negeri Tarutung, 2018)
AbstractIn this article I would like to discuss about one of the popular cultures that is a film entitled “Tanda Tanya” (Question Mark) by focusing on its narrative. The film was produced by Indonesian producer to provoke religious pluralism, but at the end the film raised a series of controversies by the public due to the issue it brings. I herewith want to see how we understand the film as a product of popular culture and understanding the story based on the theological concept of religious pluralism. Finally, I will see how such a film gives a contribution for Indonesian Religious Plurality.Keywords: Tanda Tanya, religious plurality